Analysis of Trends and Factors Affecting Indonesian Swallow Nest Exports to China for The 2020–2025 Period - Dewi Sinta (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study analyzes the trends and determinants of Indonesian swallow nest exports to China during the 2020 to 2025 period using an empirical descriptive mixed methods approach. Quantitative evidence was derived from secondary time series data obtained from the Central Bureau of Statistics and the Directorate General of Customs and Excise, covering export volume, export value, and export price indicators. Qualitative evidence was collected from academic literature, policy documents, and international trade studies to explain the underlying drivers of export performance. The findings indicate that Indonesian swallow nest exports experienced a strong upward trajectory after the pandemic period, supported by increasing Chinese demand and expanding market access. Export price dynamics revealed substantial fluctuations, reflecting market adjustment processes, seasonal demand patterns, and changing supply conditions. The average export price remained relatively stable despite temporary corrections, indicating the resilience of swallow nests as a premium export commodity. Internal factors such as production capacity, product quality, processing technology, certification, and logistics efficiency were identified as major determinants of competitiveness. External factors including import regulations, food safety requirements, exchange rate movements, and international competition also significantly influenced export performance. Strategic efforts focused on quality upgrading, digital traceability, certification enhancement, and market diversification are essential for sustaining long term export growth and strengthening Indonesia’s position in the Chinese market.